ANALISIS DAMPAK KEBERADAAN PLBN ENTIKONG TERHADAP PERUBAHAN SOSIAL MASYARAKAT DI DESA ENTIKONG - Oftapiana, Elina; Bahari, Yohanes; Ramadhan, Iwan (Universitas Tanjungpura, 2023)
The purpose of this research is to ascertain how the Entikong PLBN affected social change in the Entikong Village community. This exploration strategy utilizes a subjective and enlightening methodology. Information assortment strategies utilized are perception, meetings, and documentation. The heads of Sontas Hamlet, Entikong, Entikong Tapang, and Entikong Benuan were the four informants in this study. The consequences of this study demonstrate that there have been changes in the security framework in the at various times with the presence of the Entikong PLBN. Community activities are becoming more smoothly as a result of social change, with both visiting, seeking treatment, shopping, and selling crops to neighboring countries, community integration is increasing, the quality of individuals or communities is getting better, people's mobility is getting faster, people's mindset is getting wider and develop. The negative impact of social change is that social conflict between communities has not yet been found, and environmental pollution occurs around the Entikong PLBN area caused by the community or visitors who litter.